The Concept of Restorative Justice in Criminal Procedure Law through The Rehabilitation Process: Integrated Assessment at The National Narcotics Agency of Bone Regency - Muljan, Muljan; Nawawi, Jumriani (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The study discusses the